2021
DOI: 10.1017/s0033291721000465
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent social networks matter for suicidal trajectories: disparities across race/ethnicity, sex, sexual identity, and socioeconomic status

Abstract: Background Examining social networks, characterized by interpersonal interactions across family, peer, school, and neighborhoods, offer alternative explanations to suicidal behaviors and shape effective suicide prevention. This study examines adolescent social networks predicting suicide ideation and attempt trajectories transitioning to adulthood, while revealing differences across racial/ethnic, sex, sexual identity, and socioeconomic status. Methods Participants included 9421 high sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…Some research has also found that families with adaptability problems are at higher risk of suicidal behaviors [ 83 ]. On the contrary, higher cohesion in the family is a protective factor for depressive symptoms in adolescents [ 84 ] and this has served as a basis for research studying family cohesion as a protective factor for suicidal behavior in young people [ 85 ]. However, more studies are still required in this field to deepen these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has also found that families with adaptability problems are at higher risk of suicidal behaviors [ 83 ]. On the contrary, higher cohesion in the family is a protective factor for depressive symptoms in adolescents [ 84 ] and this has served as a basis for research studying family cohesion as a protective factor for suicidal behavior in young people [ 85 ]. However, more studies are still required in this field to deepen these associations.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated there was a causal pathway from social network strain (due to adverse childhood experiences) to suicidal ideation among middle-aged adults [ 24 ]. Social networks during adolescence influenced the odds of belonging to distinct suicidal trajectories [ 50 ]. Family cohesion protects youth from being in high-risk developmental courses of suicidal behaviors [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used hierarchical agglomerative clustering because it is robust to different types of data distributions and typically produces a dendrogram that visualizes the data structure to help determine the optimal cluster number, and because it has shown promise in identifying underlying patterns from clinical profiles. [41][42][43][44][45] Besides producing the dendrogram, we calculated 14 measures of clustering models provided by 'NbClust' software 46 to determine the optimal number of clusters, i.e., patterns of SDoH. More details and rationale for these methods can be found in the eMethods 2 and 3 in the Supplemental Online Content.…”
Section: Discussionmentioning
confidence: 99%